Fluorescein angiography in patients undergoing hemodialysis - Kishimoto, Taketoshi; Yamamoto, Mitsuhiro; Maekawa, Masanobu; Umeda, Masaru; Iwata, Hiroyuki; Izumi, Nobuhide; Yasumoto, Ryouji (Journal of Japanese Society for Dialysis Therapy, 1993)
Fluorescein angiography is one of the most important tools in diagnosing retinal-choroidal diseases, and sodium fluorescein (NaFI) is widely used as a contrast medium. In the present study, we examined the pharmacokinetics of NaFI in patients undergoing hemodialysis (HD). NaFI, 500mg, was injected into 4 HD patients with ophthalmological complications, and HD was started immediately after fluorescein angiography had been completed. Changes in plasma concentrations and clearance of NafI were studied using a spectrophotometer, and the following results were obtained. Four hours after initiating HD treatment, the plasma concentration of NaFI had decreased to 17.5% of the initial concentration. The in-vivo clearance of NaFI during HD was 35.51±13.90ml/min (Mean±SD). The half life of NaFI in HD patients on a day without dialysis was extremely prolonged compared to those in non-dialyzed patients. Because of these results, together with the relatively good dialysability of NaFI, immediate HD after fluorescent angiography should be considered for the removal of residual contrast medium.